The Influence of Student Activity in Discussions and the Quality of Teaching Material Design on the Understanding of Islamic Education Material - Sari, Yuni Purnama; Islahiah, A’idatul; Khomah, Isti; Hanifah, Abu; Abdullah, Rifki; Ruswandi, Uus (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
The development of digital technology requires students to have a strong understanding of ethics, especially in the use of social media in accordance with Islamic teachings. However, the effectiveness of Islamic Religious Education (IRE) learning is often influenced by classroom dynamics and the quality of available learning resources. This study aims to analyze the influence of student discussion activities and the quality of teaching materials on IRE comprehension, particularly regarding social media etiquette. The research method used is quantitative, with a causal-associative approach. The research sample consisted of 148 high school students selected through purposive sampling. Data were collected using structured questionnaires and analyzed using multiple linear regression to examine partial and simultaneous effects. Significant findings in this study indicate that: (1) Discussion activity has a positive and significant impact on student understanding; the initiative to argue and ask questions has been proven to strengthen mastery of the material. (2) The quality of systematic and relevant teaching materials significantly facilitates students’ absorption of information. (3) Simultaneously, both variables contribute 55.9% ($R^2 = 0.559$) to student understanding, while other factors influence the rest. The study concludes that collaboration between active learning processes and effective learning media is the key to mastering the material. The implication of this research for educators is the need to design teaching materials rich in contextual case studies and to create interactive discussion spaces. Integrated improvements in the quality of these two aspects can significantly minimize the misuse of social media among adolescents by strengthening their understanding of Islamic values.